2018
DOI: 10.1155/2018/7628037
|View full text |Cite|
|
Sign up to set email alerts
|

Evans Blue Dye: A Revisit of Its Applications in Biomedicine

Abstract: Evans blue (EB) dye has owned a long history as a biological dye and diagnostic agent since its first staining application by Herbert McLean Evans in 1914. Due to its high water solubility and slow excretion, as well as its tight binding to serum albumin, EB has been widely used in biomedicine, including its use in estimating blood volume and vascular permeability, detecting lymph nodes, and localizing the tumor lesions. Recently, a series of EB derivatives have been labeled with PET isotopes and can be used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 100 publications
1
70
0
3
Order By: Relevance
“…BBB impairment was revealed by EB extravasation into brain tissue indicative for plasma protein passage into brain tissue. EB remains the most commonly used marker of BBB integrity [84,85]. Among the strengths of EB for studying BBB integrity are its immediate visibility and quantifiability allowing for group comparisons without usage of radioactive indicators [5,36,86].…”
Section: Discussionmentioning
confidence: 99%
“…BBB impairment was revealed by EB extravasation into brain tissue indicative for plasma protein passage into brain tissue. EB remains the most commonly used marker of BBB integrity [84,85]. Among the strengths of EB for studying BBB integrity are its immediate visibility and quantifiability allowing for group comparisons without usage of radioactive indicators [5,36,86].…”
Section: Discussionmentioning
confidence: 99%
“…Extravasation of dyes and changes in transendothelial electrical resistance are often used to measure permeability of the BBB barrier in vivo and in vitro. For example, Evans blue is widely regarded as the standard measurement of BBB permeability and its extravasation has been used by numerous studies to quantify BBB breakdown in vivo [ 33 37 ], despite some reported limitations [ 38 40 ]. Transport of macromolecules larger than 5 nm, such as the 40-kDa dextran, occurs through the transcellular pathway (through the cell body regulated by the cell membrane lipid bilayer) [ 41 44 ] that is regulated in part by cytoskeleton proteins such as actin and is altered by TNF-α activation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous injection of Evans Blue was used to evaluate the changes in vascular permeability of the inflamed paw. Evans Blue is a tracer that binds to albumin and is used as an index of plasma protein leakage into tissue [19]. After subplantar injection of Fig.…”
Section: Effects Of Lius On Vascular Permeabilitymentioning
confidence: 99%